Erdoğan’s Authoritarian Neoliberalism Goes to Cyprus. What are the Chances of Success of The Imported Authoritarian Neoliberal Model? - Stelgias, Nikolaos (Advances in Social Sciences Research Journal, 2023)
The study seeks to advance the notion of authoritarian neoliberalism by discussing how the exportation of the authoritarian neoliberal model interacts with a closed society experiencing socio-economic upheaval. The paper follows the efforts made by a foreign power, such as Turkey, to assure the survival of an internationally non-recognised entity, such as the ’TRNC’, via the neoliberal transformation of its economy and the imposition of alien political strategies and social values. The paper intends to argue that the authoritarian imposition of conservative and neoliberal policies on a society by a foreign actor doesn’t necessarily produce the desired outcome. Instead, by leaving behind accumulated unsolved problems and by reproducing social and political inequalities it can raise concerns about the sustainability of the structure that the neoliberal policies were designed to support.